Identifikasi Kebutuhan Fitur Tambahan untuk Penerapan RME di Klinik KIA-Ibu Hamil Puskesmas Tegalrejo - Zahra Nabila Adistya Hariyanto; Khofifah Nur Meirawanti; Savitri Citra Budi; Kamal Burhanuddin (J-REMI : Jurnal Rekam Medik dan Informasi Kesehatan, 2023)
Tegalrejo Primary Health Care has been using SIMPUS to organize EMR since 2019. The existence of regulations requiring the use of EMR in all health facilities beginning in 2022 emphasizes the importance of preparing for EMR implementation in clinics that haven't implemented it, such as the Maternal and Neonatal Health Clinic for Pregnant Women at Tegalrejo Primary Health Care. The aim of this research is to identify the features and data items required by the Maternal and Neonatal Health Clinic for Pregnant Women to implement EMR. The analysis used fishbone diagram with a descriptive method and a qualitative approach. The material factor: the existing EMR system hasn't been able to meet the needs of medical records required by midwives, the machine factor: the performance of the available computers running slowly, the methods factor: the medical record documentation was still manual, and the officers hadn't proposed the formal application for the development of SIMPUS for pregnant women, the man factor: the officers hadn't produced an overview of the needs for EMR for pregnant women, officers' hectic working hours hindered officers from submitting EMR. Identifying needs comprises adding and reducing data items required to maximize EMR deployment.